Effect of Specimen Size and Shape on Strength of Concrete - Zabihi, Niloufar (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: Testing the mechanical properties (especially compressive strength and tensile strength) of concrete is one of the most crucial stages of construction works. To control the quality of concrete, there are various moulds that are used for casting concrete samples during concreting works according to different standards at different countries. On the other hand, it is known that different shapes and sizes of concrete samples can cause variations in results of compressive strength or splitting tensile strength. This research concentrated on the effect of specimen sizes and shapes on compressive and splitting tensile strength of concrete, cured at different conditions and tested at both early and late ages. At the end of experimental study, hardened density, non-destructive tests (i.e. rebound hammer and PUNDIT), compressive strength and splitting tensile strength for different curing conditions were performed and some analyses were done to obtain conversion factors and relations among these factors and results. The results of analyses indicate that for all testing conditions, there is a strong influence of variation of size and shape of the specimens. In some cases, by changing the curing conditions, the change of trend of experimental results was not significant, for example the results of PUNDIT test. However, by changing testing age, there was a strong alteration in the results and their trends. Keywords: size effect, shape effect, compressive strength, splitting tensile strength, rebound hammer, PUNDIT, curing regime, conversion factors. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Yapı işleri sırasında belirlenmesi gereken en önemli özellikler betonun basınç mukavemeti dayanımı ve yarmada çekme dayanımıdır. Kalite kontrolu için ise alınması gereken numune boyutu ve şekli ise standartlara ve ülkelere göre farklılıklar göstermektedir. Diğer taraftan ise, deneye tabii tutulan numune boyutu ve şekilinin betonun basınç mukavemeti ve yarmada çekme dayanımı sonuçlarında farklılıklar yaratacağı bilinmektedir. Bu çalışmada esas olarak aynı beton karışımından yapılan farklı numune boyutları ve şekillerinin betonun özelliklerine olan etkileri araştırılmıştır. Bu beton numuneler iki farklı ortamlarda kür (hava, su) edilmiş ve iki değişik yaşlarda (yedi gün, yirmisekiz gün) deneylere tabii tutulmuşlardır. Yapılan deneylerin sonuçları kullanılarak numuneler arasındaki çevirme katsayıları bulunmuştur (basınç mukavemeti ve yarmada çekme dayanımı için). Bu çalışma sırasında yapılan deneyler ise katı yoğunluk, tahribatsız deney metodu olan beton çekiçi ve PUNDIT, basınç mukavemeti ve yarmada çekme dayanımıdır. Tüm betonlar farklı kür şartlarında bekletılmiş ve iki değişik yaşta deneylere tabii tutulmuşlardır. Yapılan analizlere göre beton numune şekil ve boyutlarının betonun özellikleri ve numune-boyut değişim katsayıları üzerinde çok etkili olduğu görülmüştür. Anahtar Kelimeler: boyut etkisi, şekil etkisi, basınç mukavemeti, yarmada çekme dayanımı, beton çekici, PUNDİT, kür rejimi, çevirme katsayısı.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2012. Supervisor: Assoc. Prof. Dr. Özgür Eren.
Keywords: Civil Engineering; Performance of Concrete; Concrete - Structural Engineering; Concrete - Testing; Size Effect - Shape Effect - Compressive Strength - Rebound Hammer - PUNDIT - Curing Regime - Conversion Factors